The Influence Of Work Environment And Work Motivation On Employee Work Productivity At The North Sumatra Province DPRD Office - Tampubolon , Sinta Romarito; Insan , Yalzamul; Robain , Wilchan (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the influence of the work environment and work motivation on employee productivity at the Secretariat of the Regional House of Representatives (DPRD) of North Sumatra Province. Specifically, the study examines the effects of the work environment and work motivation both partially and simultaneously on work productivity. The approach used is quantitative with a survey method, involving the distribution of questionnaires to 71 respondents. Collected data were analyzed using multiple linear regression with the help of SPSS version 26. The results show that partially, the work environment does not have a significant effect on employee productivity (significance value 0.457 > 0.05), while work motivation has a significant partial effect on employee productivity (significance value 0.022 < 0.05). Simultaneously, both independent variables have a significant effect on employee productivity with a significance value of 0.031 and a coefficient of determination (R²) of 0.096. This indicates that 9.6% of the variation in employee productivity can be explained by these two variables.